THE EFFECT OF SELF REGULATED LEARNING MODEL TOWARDS MOTIVATION AND COMMUNICATION INFORMATION TECHNOLGY LEARNING ACHIEVEMENT OF THE STUDENTS CLASS VIII SMP NEGERI 1 BANJAR IN 2011/2012 - Komang Hari Santhi Dewi (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
The study aimed at finding out (1) the effect of self regulated learning (SRL) model towards learning achievement in communication and information technique of the students class VIII SMP Negeri 1 Banjar, (2) students motivation towards the implementation of SRL model, (3) students’ responses towards the implementation of SRL model.It was a quasi experimental study employing a Post-test Only Control Group  Design. The population of the study were all students class VIII SMP Negri 1 Banjar in 2011/2012. The study involved a number of 65 samples consisting of students in class VIII-C and VIII-E. Class VIII-C became an experimental group, while class VIII-E as a control group. There were two different variables in this study, those are (1) independent variable: SRL model, and (2) dependent variable: motivation and student learning achievement. The data were collected by using multiple choice achievement test to measure the cognitive domain, as well as psychomotor test to measure the psychomotor domain. The data then analyzed by using prerequisite test involving normality, homogeneity, and t-test. While in terms of response and motivation, questionnaires were used.The findings indicated that (1)  there was a significant  effect of self regulated learning (SRL) model of the students. The average score of the students joining direct instruction was 32.02 with standard deviation of 2.92, and the average scores of the students joining SRL model was about 38.50 with standard deviation of 2.33. It indicated that students joining SRL model got higher scores than those a direct model, (2) students motivation average value of the students during the implementation of SRL model was about 72.15, with a percentage of final session of about 21.88% with very high motivation, 68.75% with high motivation, and 9.38% with average motivation. (3) the average value of students’ responses as about 79.63 with  25% of very positive responses, 65.63% of positive responses, and 9.38% of sufficiently positive responses towards the implementation of SRL model.